Problems and practicalities in student caseload holding. - Fry, Jane; Rawnson, Stella; Lewis, Paul (British Journal of Midwifery, 2011)
Nursing and Midwifery Council (NMC) standards require higher educational institutions (HEI) to introduce opportunities in which student midwives are involved in the care of a small group of women throughout their childbearing experience, enabling them to gain experience of continuity of care and carer through caseload holding (NMC, 2009a:16). Bournemouth University (BU) first introduced student caseloading in 1996, and the experience has enabled us to evaluate, refine and develop this approach to learning. In this article, the problems and practicalities encountered over the years while supporting students and mentors through the everyday delivery of caseload holding will be considered. Using a case study approach, this article focuses on situational experiences in the antenatal, intrapartum and postnatal periods. The lessons learnt and resultant consequence for the development and delivery of caseload holding at BU have been important in refining our approach. It is through such reflections that we hope to assist other HEIs and midwives in practice to develop and deliver similar approaches to learning.